La place des habitants dans la patrimonialisation conflictuelle du logement social - Géraldine Djament-Tran (EchoGéo)
At a time of crisis in metropolitan housing for ordinary people, this article uses the case of Plaine Commune to show that mobilizing people to promote the heritage status of social housing remains exceptional (“cité Meissonier” in Saint-Denis). Rather, the promotion of heritage is based on the views of experts (“cité Renaudie” at Villetaneuse), whilst intercommunality promotes residential activism (as in the garden-suburb of Stains). Promotion of heritage is threatened in two ways: mobilization against the notion by residents experiencing terrible social problems (“Cité des Poètes” in Pierrefitte), or the departure of such people away from social housing.